Novel orodispersible compositions of nutraceuticals prepared by the technology of extrusion-spheronization - Namita Desai, Satish Jain, P. S. Pirthipal Singh, Purnima Amin (Journal of Applied Pharmaceutical Science, 2017)
European Medicines Agency (EMA) characterized liquid formulations as most appropriate for pediatric population but this includes drawbacks of lesser stability, more shelf space and dosing error in comparison to solid oral dosage forms. Orodispersible systems hold great promise for children as they are easy to administer, do not require additional water, are difficult to spit out, stable, thus combining advantages of solid and liquid oral dosage forms. The aim of the present research was development of orodispersible pellets of Calcium and Cholecalciferol, as nutraceuticals using the technology of Extrusion – Spheronization. Calcium deficiency is manifested in the bones and teeth of all young animal species, including humans. Effects include stunted growth, poor quality bones and teeth, bone malformation. The experimental work included optimization of the extrusion – spheronization processing parameters and choice of excipients, which critically affected the product quality to produce orodispersible pellets. The developed orodispersible pellets had satisfactory quality control parameters and formed soft palatable mass on contact with salivary fluid which could be easily swallowed. The in vitro dissolution studies indicated rapid release of active and the pellets were found to be stable. An additional advantage of these orodispersible pellets is sprinkling over soft food, juices etc for food fortification prior to administration.
Keywords: Orodispersible pellets, Calcium and Cholecalciferol, Extrusion – Spheronization, pediatric.